Islandia: Agrarian Society Meets Global Capitalism. Issue 3 (January 2018) - Abbott, Carl
Abstract : Austin Tappan Wright's novel Islandia (1942) describes an imaginary nation whose residents debate choices of economic and social policy during the era of Great Power imperialism that preceded the First World War. A framing plot pivots on efforts by European nations to force Islandians to open their closed agrarian economy to resource development and trade. In creating Islandia's diplomatic dilemma, Wright references the history of European imperialism contemporaneous with the novel's 1908 setting. The same dilemma and debates resonated in the 1920s, when Wright was composing the novel, and echo in the present neoliberal era in which developed economies claim the natural resources of other nations as a matter of right and progress.